1968
DOI: 10.1080/00021369.1968.10859251
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Lipoprotein Lipases of Microorganisms

Abstract: The production of lipoprotein lipases by Pseudomonas sp. M-12-33 was improved by an increased aeration. Glucose stimulated the growth of the bacterium but reduced the enzyme production in Bouillon medium. Olive oil remarkably increased the production of lipoprotein lipases but the effect was cancelled by calcium carbonate. Stearic and palmitic acids were as effective as olive oil, but capric and caprylic acids inhibited the enzyme production. Urea was proved to be very effective as '" nitrogen source for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It seems likely that the lipid plays an essential role in the formation of cholesterol esterase by P. fluorescens. A similar lipid require ment for enzyme production has been observed with lipoprotein lipase of Pseudomonas sp., 22) lipases of Candida paralipolytica23) and Geotri chum candidum Link. 24) The time course of the culture of Pseudo monas fluorescens showed that the enzyme for mation in the culture fluid was observed in an early stage of growth when cells were not prone to lysis.…”
Section: Effect Of Various Lipids On Enzyme Pro Ductionmentioning
confidence: 99%
“…It seems likely that the lipid plays an essential role in the formation of cholesterol esterase by P. fluorescens. A similar lipid require ment for enzyme production has been observed with lipoprotein lipase of Pseudomonas sp., 22) lipases of Candida paralipolytica23) and Geotri chum candidum Link. 24) The time course of the culture of Pseudo monas fluorescens showed that the enzyme for mation in the culture fluid was observed in an early stage of growth when cells were not prone to lysis.…”
Section: Effect Of Various Lipids On Enzyme Pro Ductionmentioning
confidence: 99%
“…It seems likely that the lipid plays an essential role in the formation of cholesterol esterase by P. fluorescens. A similar lipid requirement for enzyme production has been observed with lipoprotein lipase of Pseudomonas Sp., 22) lipases of Candida paralipolytica 23 ) and Geotrichum candidum Link.24J…”
Section: Streptomycesmentioning
confidence: 99%